Analysis of the Creep Behaviour of Polypropylene - André, José Reinas (2005)
In this work, creep data for a polypropylene (PP) were obtained at different levels of tensile stress and temperature, and were then analysed in the light of a model developed, which is based on physical mechanisms (at the molecular scale) responsible for the material’s behaviour, considering that a minimum retardation time does exist. The model yields very good agreement with the experimental data and physically meaningful theoretical parameter values.